Pengaruh Pelatihan SDM, Motivasi, dan Lingkungan Kerja Terhadap Kinerja ASN Disporapar Kabupaten Pidie Jaya - Gunawan Gunawan; Endang Syahriani; Sri Yanna (Aceh Cooperative Care, 2026)
This study examined employee performance by involving human resource training, internal factors such as employee motivation, and work environment support at the Pidie Jaya Regency Youth and Sports Agency (Disporapar). The study used quantitative associative research and statistical analysis using path models to obtain empirical results from 42 employee respondents. The findings revealed: (1) a strong causal relationship exists between human resource training, work motivation, and the work environment on employee performance. (2) A combination of these three factors, direct and indirect, influences performance. Each factor contributed 45.69% to human resource training, 35.07% to work motivation, and 24.71% to work environment support. (3) All three factors simultaneously contributed 43.1% to employee performance.